Enhancing Environmental Sustainability Practices in Laboratories - Turan, Nouha Bakaraki; Engin, Guleda Onkal; Bilgili, Mehmet Sinan (Mehmet Sinan Bilgili, 2022)
Environmental sustainability (ES) became a serious global challenge nowadays. The importance of ES in shaping the future of the planet attracts the conscious division of society and stakeholders to incorporate this concept in their lifestyles and decisions. The embarrassing realization is that research laboratories themselves are not apart from the worst environmental offenders. This fact recently sink in pushing authorities to examine this risk by finding environmentally friendly solutions and pratices that reduce energy consumption, water usage, and waste production. Highly reputable universities and companies were the models for being greenly certified. However, the concern remains for the uncontrolled laboratories and the level of serious applications and awareness even by the certified laboratories. In this paper, the environmental threat from research laboratories will be discussed in detail proposing various green practices and management strategies that can be implemented for resources and materials used in the laboratories. Within the structure of a green laboratory, the responsibility and awareness of universities and companies will be underlined.
Keywords: Environmental sustainability; Laboratory; Green Practices; Engineering; Environmental Sciences & Ecology